Artificial β‐Double Helices from Achiral γ‐Peptides. Issue 4 (27th December 2017) - Misra, Rajkumar; Dey, Sanjit; Reja, Rahi M.; Gopi, Hosahudya N.
Abstract: Double helices are not common in polypeptides and proteins except in the peptide antibiotic gramicidin A and analogousl, d ‐peptides. In contrast to natural polypeptides, remarkable β‐double‐helical structures from achiral γ‐peptides built from α, β‐unsaturated γ‐amino acids have been observed. The crystal structures suggest that they adopted parallel β‐double helical structures and these structures are stabilized by the interstrand backbone amide H‐bonds. Furthermore, both NMR spectroscopy and fluorescence studies support the existence of double‐helical conformations in solution. Although a variety of folded architectures featuring distinct H‐bonds have been discovered from the β‐ and γ‐peptide foldamers, this is the first report to show that achiral γ‐peptides can spontaneously intertwine into β‐double helical structures. Abstract : The double helix is a common structural feature in nucleic acids and polysaccharides. However, double helix structures are not common in polypeptides except in the peptide antibiotic gramicidin A. A new class of achiral γ‐peptides, which spontaneously intertwine into parallel β‐double helices, is reported.